Competitives strategy in enhancing Malaysian firms' performance through mediating effect of liberalisation - Mohd Darus, Norazlina (2020)
The concept of competitive strategy from strategic management is imperative in the small and medium firms (SMFs) as a result of the impression of free trade known as liberalisation. The competitive strategy is aimed at reducing the negative impact of SMFs activities in the free trade. The issue of liberalisation or free trade has earned attention in academic studies in recent years and the relationship between competitive strategy and firm performance has begun to be discussed in stages but still requires more results that depend on the strategic management in the entrepreneurial field. Hence, the focus of the study is on identifying the root cause of competitive strategy as well as for examining how competitive strategy can enhance the SMFs services sectors performance in Malaysia. This study also examines the current competitive strategy and challenges of liberalisation in the Malaysian SMFs and also the effect of moderators in terms of SMF's cability and competency in achieving firm performance improvement that ultimately build a competitive strategy framework in SMFs performance enhancement in Malaysia. Guided by the theory of competitive strategy such as intellectual capital, innovation and quality, this study develops a framework to address the liberalisation barriers to achieving firm performance improvement. Survey data were collected from SMFs in services sectors in Malaysia using cross sectional study design and stratified random sampling methods. A total of 396 questionnaire forms that can be used were collected using physical collection methods and analysed with 'Covariance-Based SEM' (CB-SEM). A total of six hypotheses relationships are supported. This study found that competitive strategy component of intellectual capital, innovation, quality and firm performance were significanlty related. Similarly, liberalisation has also significantly related to perforamnce. While liberalisation pressures mediating the relationship between competitive strategy and firm performance. The effect of moderators, capability and competency of SMFs also spurred the relationship between liberalisation and firm performance. Descriptive results indicate that the implementation of liberalisation among service firms in Malaysia are still low due unawareness and understanding responses from respondents. This study makes some theoretical contributions and provides further insights on drivers and the effects of competitive strategy in Malaysia. In the perspective of strategic management, this study provides a valid framework and can be used for SMFs to provide awareness of the importance of liberalisation in their organisations. The implications of this study to policy makers, academics and industry practitioners are to raise awareness of the long-term benefits and effects of liberalisation towards better performance of the firms, and review policies on competitive strategy and regulations in Malaysia to provide policies that support regulation of free trade, incentives and initiatives that will enhance the performance of SMFs in the Malaysian services industry.